Assessing the Vulnerabilities of Bioterrorism: Challenges and Prospects - Bushra Qamar; Adeel Irfan; Javed Iqbal (National University of Modern Languages (NUML), Islamabad, 2024)
This study investigates the vulnerabilities and challenges exacerbated by bioterrorism empirically. Terrorists, organizations, and individuals deliberately use biological weapons to kill humans, animals, and plants. According to experts, the threats are multifaceted and have intensified in the modern world, such as 5th generation warfare and health crises.  The study is exploratory, employing a qualitative approach to explore the literature, policy documents, and reports released by international and national organizations. In addition, the study integrates the most recent papers published during COVID-19 to investigate the difficulties and potential of bioterrorism. The findings provide a thorough understanding of the expected dangers of bioterrorism, such as threats of theft and attack, threats to utilize biological weapons, which are cost-effective, by terrorist groups, anarchic proliferation across the globe, biological agent manipulation, and so on. During the pandemic COVID-19, several countries, including Pakistan, experienced these risks. Given all of the looming concerns stated above, precautionary actions should be implemented to avoid these threats in the event of a new international bioterror strike in the future.